(3GdeMGSHI GdeGdjI GdeJbOeI (B/s - (3TMGJI, CMeO HSjhfjs; (3HOhj, eMeO YHGSs ((3GdEScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2002)
(3GdbhGFe GdeGdjI GdehMOI aj eLGd eMGSHI GdaQhY GdeMdjI hGdGLfHjI,GdbhGFe GdeGdjI ddaQhY GdeMdjI ,GdbhGFe GdeGdjI ddaQhY GdCLfHjI (B-(3GdeMGSHI aj GdTQcGJ GdbGHVI hGdJGHYI ,GdeMGSHI Yf GdGfVeGe hGdGfOeGL,GYOGO GdbhGFe ,GdeHjYGJ GdHjfjI ddHVGFY (B-(3GdeMGSHI Yf GdJbdHGJ aj eSJhjGJ GdCSYGQ ,GdGWGQ GdYGe ,GdeOGNd GdeMGSHjI ,eOGNd GdQHW Hjf JQLeI GdbhGFe GdeGdjI GdCLfHjI hXGgQI GdJVNes
Keywords: (3GdeMGSHI (B- (3GdTQcGJs; (3GdeMGSHI GdeGdjIs